Petrographic characteristics in the central part of Kosovo - Kutllovci, Festim; Fejza, Islam (Dnipro University of Technology, 2021)
Purpose. This paper aims to provide complete identification of rock types in the Drenas region by detailed description of all types of the rocks found. The authors intended to determine interruption or continuity of all inter-formational boundaries to accurately delineate them on the ground and fully reflect on the 1: 25000 scale map, as well as to identify the nature of contact between rock types and give its detailed description. Methods. During August, September, October of 2019, the exploration field trips were carried out. Geological survey works focused on the following areas: complete identification of all rock types on the basis of studying their samples, preparation of thin sections for petrographic (only the magmatic rock), chemical and geochemical analysis. Systematic measurement of structural elements was conducted alongside with identification and description of mineral outcrops areas. Findings. Based on the study of stratigraphic units and geological description of mineral outcrop areas, we identified different types of rocks using petrography microscope preparation and chemical and geochemical analysis. The area of Drenas has the following lithostratigraphic units: gabbro diabase, harzburgite, metasandstone. Originality. The originality of the study consists in the use of optical microscope for precise identification of rocks. As a result of the research conducted in the exploration area, we have obtained a clear petrographic description of minerals composition, their texture and mineralization, which allows assessing the possibility of the area exploitation. The analyses were completed at the certified laboratory of Geology-Mining Faculty (Polytechnic University of Tirana) and Geosciences Institute. Practical implications. Petrographic study and chemical analysis led to the conclusion that the research area has Ni mineralization, which is important for the development of mining sector and the community given the environment is preserved and the adequate way of the area exploitation is applied.

Мета. Повне визначення типів гірських порід районі Дренаса шляхом їх докладного опису. Автори мали намір визначити наявність розривних порушень та охарактеризувати суцільність усіх міжпластових меж, щоб точно окреслити їх на місцевості та чітко зобразити на карті масштабу 1:25000, а також виявити специфіку контакту між гірськими породами різного типу та надати його комплексну детальну характеристику. Методика. У серпні, вересні, жовтні 2019 року були проведені польові геологорозвідувальні роботи, які були зосереджені на наступних напрямках: комплексна ідентифікація всіх типів порід на основі вивчення їх зразків, підготовка шліфів для петрографічного (лише магматична порода), хімічного та геохімічного аналізу. Аналізи були виконані у сертифікованій лабораторії Факультету геології та гірничої справи (Політехнічний університет Тирани) та дослідження проводились в Інституті геологічних наук. Систематичні вимірювання структурних елементів проводилися поряд з виявленням та описом ділянок відслонень корисних копалин. Результати. На основі вивчення стратонів та геологічного опису ділянок відслонеь діагностовано різні типи порід за допомогою петрографічної мікроскопії та хіміко-геохімічного аналізу. У районі Дренаса представлені наступні літостратиграфічні одини-ці: габро діабаз, гарцбургіт, метапісковик. Виділено чотири фази пластичної деформації геологічного району на основі структурного та мікроструктурного аналізу, а також даних щодо геоструктурного фону разом з літохроностратиграфічним аналізом. Наукова новизна. Новизна дослідження полягає у використанні оптичного мікроскопа для точної діагностики гірських порід. Встановлено чіткий петрографічний опис складу мінералів, їхньої текстури та мінералізації, що дозволяє оцінити можливість експлуатації ділянки. Практична значимість. Петрографічні дослідження та хімічний аналіз дозволили зробити висновок про те, що у досліджуваній зоні є поклади нікелевих руд, які важливі для розвитку гірничодобувного сектора та суспільства, за умови збереження навколишнього середовища та застосування належного способу експлуатації родовища.

Цель. Полное определение типов горных пород в районе Дренаса путем их подробного описания. Авторы намеревались определить наличие разрывных нарушений и охарактеризовать сплошность всех межпластовых границ, чтобы точно очертить их на местности и четко изобразить на карте масштаба 1:25000, а также выявить специфику контакта между горными породами разного типа и дать его комплексную детальную характеристику. Методика. В августе, сентябре, октябре 2019 года проведены полевые геологоразведочные работы, которые были сосредоточены на следующих направлениях: комплексная идентификация всех типов пород на основе изучения их образцов, подготовка шлифов для петрографического (только магматическая порода), химического и геохимического анализа. Анализы были выполнены в сертифицированной лаборатории факультета геологии и горного дела (Политехнический университет Тираны), а также исследования проводились в Институте геологических наук. Систематические измерения структурных элементов проводились наряду с выявлением и описанием участков обнажений полезных ископаемых. Результаты. На основе изучения стратонов и геологического описания участков обнажений диагностировано различные типы пород с помощью петрографической микроскопии и химико-геохимического анализа. В районе Дренаса представлены следующие литостратиграфические единицы: габбро диабаз, гарцбургит, метапесчаник Выделено четыре фазы пластической деформации геологического района на основе структурного и микроструктурного анализа, а также данных о геоструктурном фоне вместе с литохроностратиграфическим анализом. Научная новизна. Новизна исследования заключается в использовании оптического микроскопа для точной диагностики горных пород. Установлено четкое петрографическое описание состава минералов, их текстуры и минерализации, что позволяет оценить возможность эксплуатации участка. Практическая значимость. Петрографические исследования и химический анализ позволили сделать вывод о том, что в исследуемой зоне имеются залежи никелевых руд, которые важны для развития горнодобывающего сектора и общества, при условии сохранения окружающей среды и применения надлежащего способа эксплуатации месторождения.
Keywords: Drenas zone; mineralogical composition; petrography microscope preparation; deformation; tectonic